2009
DOI: 10.1159/000219683
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide Inhibits Choroidal Neovascularization in Rats

Abstract: Aims: Octreotide exhibits anti-angiogenic activity in animal models of retinopathy of prematurity and in clinical cases of proliferative diabetic retinopathy. In this study, we tested the applicability of using octreotide for inhibiting experimental choroidal neovascularization (CNV) in rats. Methods: Of 15 adult rats used, 3 served as non-laser-treated controls. CNV was induced in the right eye of the remaining 12 rats by laser photocoagulation. These 12 rats were divided into two groups (n = 6 each) which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
7
1
Order By: Relevance
“…Although we did not find any of the more commonly reported side effects like severe gastrointestinal problems (for example, necrotizing enterocolitis) [19] , hypothyroidism, cholelithiasis [20,21] and retinal problems [22,23] , we did find a relatively high occurrence of PPHN which required treatment.…”
Section: Discussioncontrasting
confidence: 77%
“…Although we did not find any of the more commonly reported side effects like severe gastrointestinal problems (for example, necrotizing enterocolitis) [19] , hypothyroidism, cholelithiasis [20,21] and retinal problems [22,23] , we did find a relatively high occurrence of PPHN which required treatment.…”
Section: Discussioncontrasting
confidence: 77%
“…Recently published methods include describing CNV staining on FA relative to the size of optic nerve head (Sickenberg et al, 1999), by measuring diameter of CNV lesion along an axis (Criswell et al, 2008), by assessing lesion size based on the presence or absence of leakage (Dobi et al, 1989; Husain et al, 1999; Kanai et al, 2000; Obana et al, 2000; Tobe et al, 1998; Zacks et al, 2002), by using a qualitative grading method (Nishiwaki et al, 2002; Qu et al, 2009;Wang et al, 2007), and by measuring the CNV staining perimeter using imaging software (Funakoshi et al, 2006). None of these methods have been validated and many of them are arguably unable to detect small, but significant, changes in CNV lesion size due to their subjective and categorical (mild, moderate, severe) nature.…”
Section: Discussionmentioning
confidence: 99%
“…However, results vary considerably depending on which technique is used to quantify the CNV lesions, making it difficult to compare results among the above referenced studies. For instance, some methods are unable to detect small, but significant, changes in CNV lesions due to their subjective and categorical nature, such as classifying lesions as mild, moderate, severe or based on the presence or absence of leakage (Dobi et al, 1989; Husain et al, 1999; Kanai et al, 2000; Nishiwaki et al, 2002; Obana et al, 2000; Qu et al, 2009; Tobe et al, 1998; Wang et al, 2007; Zacks et al, 2002). Therefore, the purpose of this study is to develop new and compare existing methods of analyzing laser-induced CNV, on both choroidal mounts and FAs, to determine their validity and reliability in order to make recommendations that may improve the consistency of CNV reporting.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the formation of subretinal neovascularization arising from the choriocapillaris reaches maximal approximately 14 days post-laser induction [22][23][24] . In the present study, similar laser parameters to those in the previous studies were adopted, and the changes of CNV lesions and some hypoxia-regulated genes were detected on day 14 of rat CNV model after laser injury.…”
Section: Discussionmentioning
confidence: 99%